Impacts of colonization on Indigenous Two-Spirit/LGBTQ Canadians' experiences of migration, mobility and relationship violence. (September 2019) - Ristock, Janice; Zoccole, Art; Passante, Lisa; Potskin, Jonathon
An exploratory, community-based research project examined the paths of migration and mobility of Canadian Indigenous people who identify as Two-Spirit, lesbian, gay, bisexual, transgender and/or queer (LGBTQ). A total of 50 participants in Winnipeg, Manitoba and Vancouver, British Columbia, Canada were interviewed, many of them telling stories about the multiple layers of domestic violence, violence in communities, state and structural violence that they experienced. In order to better respond to relationship violence experienced by Indigenous Two-Spirit/LGBTQ people it is necessary to understand the specific and historical context of colonization in which relationship violence occurs. We further need to align our efforts to end relationship violence with broader anti-violence struggles.